IMPLEMENTASI MANAJEMEN PENINGKATAN MUTU BERBASIS SEKOLAH (MP-MBS) DI MA PLUS YANMU NW PRAYA - Aldi Ferdiansyah; Nur Maulidiyah Sa'adah; Subiyantoro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education plays a crucial role in shaping a quality generation. To achieve this goal, Indonesia continues to strive to improve the quality of its education. One of the popular efforts is the implementation of School-Based Quality Improvement Management. (MP-MBS). This research aims to determine the effectiveness of implementing school-based quality improvement management and its impact on the quality of education at MA Plus Yanmu NW Praya. This type of research uses descriptive research with a qualitative approach. Data collection techniques included observation, interviews, and documentation. Data analysis techniques used the Miles and Huberman analysis technique, which involves data reduction, data presentation, and conclusion drawing. Meanwhile, the data validity technique uses triangulation of techniques and triangulation of sources. The research results show that MA Plus Yanmu NW Praya has successfully implemented School-Based Quality Improvement Management (MPMBS) by integrating the government curriculum and pesantren curriculum, producing graduates who excel academically, are globally competitive, and possess Islamic character. Excellence in English and Arabic, supported by human resource management, facility upgrades, and technology, has become the main competitive edge. However, challenges such as curriculum integration, infrastructure, and time management are still being faced. To address this, the madrasah optimizes communication, teacher training, and facility improvements, strengthening its position as an excellent educational model and positively contributing to society.